(untitled) (The Strategic Review for Southern Africa, 2020)
This essay marks the maturing of South Africa's democracy since it was established in 1994. It raises questions as to whether the democratic dispensation has fulfilled what it promised, and it examines the reasons thereof. In essence it reasons that democracy has failed the people of South Africa because it lacks democratic accountability, and a firm foundation on the expressed will of the people. The theological and ethical factors in addressing the failings of a democratic system come into view. The essay concludes with an affirmation of the essential character of the church in promoting and defending justice in the world. One-dimensional thought is systematically promoted by the makers of politics and the purveyors of mass information. Their universe of discourse is populated by self-validating hypotheses which necessarily and mono-politically repeated, become hypnotic definitions and dictations... The products indoctrinate and manipulat; they promote a false consciousness that is immune against falsehood… This emerges a pattern of one-dimensional thought and behavior… Herbert Marcuse: One-Dimensional Man (1964)